Efforts to Improve Elementary School Students' Thinking Skills: Science Learning Through Questioning and Discussion Methods - Sintawati, Siska; Saputri , Intan; Hasyim, Ahmad Furqoni; Zaitun (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2024)
This study aims to determine whether discussion and question-answer methods can influence and enhance the critical thinking skills of 4th-grade students at UPTD SDN Socah 2, especially in science learning. In the first cycle of the study, it was found that the overall student score was 60%, which did not meet the predetermined success indicator of 80%. Therefore, a second cycle was conducted to rectify the previous errors, resulting in an improved score of 94.20%. Thus, it can be concluded that the implementation of question-answer and discussion methods can stimulate students' learning motivation, consequently enhancing their critical thinking skills as a form of problem-solving, particularly in science learning regarding the properties of matter and its changes.